Two reliable protocols for assessing maximal-paddling performance in surfboard riders - Loveless, D. J.; Minahan, C. (Journal of Sports Sciences, 2010)
Reliability of maximal-paddling performance in surfboard riders (surfers) was determined. Peak power output was measured in 11 male surfers (age 17 ± 1 years, body mass 61.1 ± 9.2 kg, stature 1.71 ± 0.08 m) during six 10-s maximal-intensity paddling tests on a swim-bench ergometer (laboratory tests) over 2 days (Days 1 and 2). In addition, peak speed was measured during six 10-s maximal-intensity paddling tests performed in a swimming pool (field tests). Two types of field tests were performed: (1) three trials of arm paddling and leg kicking and (2) three trials of arm paddling only. There were no differences among the laboratory tests, or among the arm paddling or arm paddling plus kicking field tests. Intraclass correlation coefficients (r) for the laboratory test were 0.99 (P < 0.01) for the six trials, 0.99 (P < 0.01) for Trials 1 and 2, and 0.98 (P < 0.01) for Trials 1 and 4 (i.e. Day 2, Trial 1). Equivalents for the field tests were 0.99 (P < 0.01) for three trials of arm paddling and kicking and 0.99 (P < 0.01) for arm paddling only. In conclusion, maximal-paddling performance can be measured reliably both in the laboratory during swim-bench ergometry and in the field in a swimming pool.